Pregnant women with fetal abnormalities: the forgotten people in the abortion debate. - de Crespigny, L; Savulescu, J (Australasian Medical Publishing Company, 2008)
Abortion law reform focuses on early abortion. Women wanting to have a family who have a fetal abnormality detected later in pregnancy are neglected in the debate and harmed by the consequences of current legal uncertainty. Unclear abortion laws compromise: the quality of prenatal testing; management when an abnormality is found; and patient care, through obstetricians' fears of legal repercussions. Women carrying a fetus with an abnormality are being denied abortion, even when the abnormality is so severe that non-treatment would be an option if the baby were born. Many women are likely to refuse to consider motherhood if they are denied appropriate prenatal testing and access to abortion if serious abnormalities are detected. Current abortion laws result in discriminatory and inconsistent practices, where access to prenatal testing and termination of pregnancy depends on location, the values of the treating doctor or hospital ethics committee, and a woman's personal resources. Legal certainty is needed to reduce the suffering of couples wanting to have a family.